2012
DOI: 10.1371/journal.ppat.1002967
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger Receptor Class A Plays a Central Role in Mediating Mortality and the Development of the Pro-Inflammatory Phenotype in Polymicrobial Sepsis

Abstract: Sepsis is a frequent complication in critical illness. The mechanisms that are involved in initiation and propagation of the disease are not well understood. Scavenger receptor A (SRA) is a membrane receptor that binds multiple polyanions such as oxidized LDL and endotoxin. Recent studies suggest that SRA acts as a pattern recognition receptor in the innate immune response. The goal of the present study was to determine the role of SRA in polymicrobial sepsis. SRA deficient (SRA−/−) and C57BL/6JB/6J (WT) male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 45 publications
4
30
0
1
Order By: Relevance
“…In addition, we performed gram stains on the blood bacteria grown on tryptic soy agar. The predominant bacteria present were Lactobacilli and Escherichia coli (Supplemental data) which was completely consistent with published work by other investigators [38].…”
Section: Clp-sepsis Modelsupporting
confidence: 90%
“…In addition, we performed gram stains on the blood bacteria grown on tryptic soy agar. The predominant bacteria present were Lactobacilli and Escherichia coli (Supplemental data) which was completely consistent with published work by other investigators [38].…”
Section: Clp-sepsis Modelsupporting
confidence: 90%
“…We found reduced activity of NF-κB in the organs from cxcl1 −/− mice post-CLP. Although NF-κB activity is important for survival after PMS (4, 30), it is questionable whether this phenomenon contributes to efficient neutrophil recruitment and bacterial clearance. NF-κB activation has been demonstrated to be essential for neutrophil recruitment due to its contribution to the expression of adhesion molecules, such as ICAM-1 (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular and cellular mechanisms that regulate immune responses to polymicrobial sepsis are not completely understood. Prior studies have shown that deletion of nucleotide-binding oligomerization domain-2 (NOD2) receptors or the scavenger receptor class A leads to host protection (3, 4). In contrast, reduced survival and diminished production of cytokines and chemokineswas observed in Stat-2 −/− mice during lipopolysaccharide (LPS)-mediated endotoxic shock, indicating a crucial role for STAT-2 in host defense (5).…”
Section: Introductionmentioning
confidence: 99%
“…Scavenger receptor SRA is expressed primarily on myeloid cells, including DCs, and functions as an innate pattern recognition receptor (Ozment et al, 2012;Yu et al, 2011;Seimon et al, 2006). In addition to the established roles that SRA plays in lipid metabolism, atherosclerosis and pathogen recognition, the evidence also demonstrates that SRA serves as a suppressor of vaccine-induced antitumor immunity Qian et al, 2011;Guo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%